Ralph Compton terror trail [large type] - Brandt, Lyle, 1951-; Compton, Ralph (Compton, Ralph. Trail drive series., 2022)
"The daughters of a New Mexican rancher must help their father recover a stolen herd in this thrilling new novel in the bestselling Trail Drive series. In the early days of the Mexican Revolution guerrillas led by Francisco "Pancho" Villa raid a ranch in Dona Ana County, New Mexico Territory. They abscond with a herd of saddle horses earmarked for sale to the U.S. Army, wounding rancher Alejandro Aguirre and killing his only son, Eduardo, in the process. When the army commander and his superiors in Washington, D.C. refuse to violate Mexican sovereignty with a punitive raid, Alejandro's twin daughters, Dolores and Yolanda, must step up. Together they lead a crew of ranch hands and friendly members of the Mescalaro Apache tribe to recover the herd. A perilous road lies ahead, but the sisters will stop at nothing to find justice for their fallen brother and reclaim what was stolen"--